2021
DOI: 10.1177/09596836211060487
|View full text |Cite
|
Sign up to set email alerts
|

Solar-type periodicities in the climate variability of Northern Fennoscandia during the last three centuries: Real influence of solar activity or natural instability in the climate system

Abstract: Fifteen proxy records of summer temperature in Fennoscandia, Northern Europe and in Yamal and Taymir Peninsulas (Western Siberia) were analyzed for the AD 1700–2000 period. Century-long (70–100 year) and quasi bi-decadal periodicities were found from proxy records representing different parts of Fennoscandia. Decadal variation was revealed in a smaller number of records. Statistically significant correlations were revealed between the timescale-dependent components of temperature variability and solar cycles o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 94 publications
(178 reference statements)
0
3
0
Order By: Relevance
“…Moreover, our analysis also explicitly assumes that there is a direct linear relationship between ST and each of the forcings. However, many studies have suggested that the relationship between solar activity and ST is subtler and more complex than a simple linear relationship to TSI (Roy 2014;Kilifarska 2015;Sfică et al 2018;Svensmark et al 2021;Stefani 2021;Ogurtsov et al 2022;Scafetta 2023;Kumar et al 2023). Similarly, concerns have been raised over the modeled climate response to volcanic forcings, e.g., Lindzen & Giannitsis (1998), Chylek et al (2020), Khaykin et al (2022).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our analysis also explicitly assumes that there is a direct linear relationship between ST and each of the forcings. However, many studies have suggested that the relationship between solar activity and ST is subtler and more complex than a simple linear relationship to TSI (Roy 2014;Kilifarska 2015;Sfică et al 2018;Svensmark et al 2021;Stefani 2021;Ogurtsov et al 2022;Scafetta 2023;Kumar et al 2023). Similarly, concerns have been raised over the modeled climate response to volcanic forcings, e.g., Lindzen & Giannitsis (1998), Chylek et al (2020), Khaykin et al (2022).…”
Section: Discussionmentioning
confidence: 99%
“…The studies by Vinay Kumar et al [16] as well as by Maxim Ogurtsov et al [17] and Potrzeba-Macrina and Zurbenko [18] highlight the future challenges and research directions, emphasizing how regional-scale atmospheric circulation can aid in understanding solarinduced climate variability. Furthermore, Wei Lu et al [19] conducted a study to explore the potential connection between the summer temperature distribution over Eurasian land and solar activity, while Thomas and Abraham [20] focused on investigating the periodicities of rainfall over Kerala, India, and sunspot numbers, and explored the possible associations between these factors.…”
Section: Introductionmentioning
confidence: 99%
“…(b). Since (1,1) is the position of dc, the coupling edge is present at coordinates(5,17), i.e., for coupled frequencies 4 and 16. The created 20th harmonic does not present any footprint in the region of the bispectrum, which is enclosed in the red line.…”
mentioning
confidence: 99%